Comparative study of aged patients with ruptured intracranial aneurysms - Kamiya, Kazuko; Ogasawara, Hidenori; Yano, Takashi; Inagawa, Tetsuji (Japanese Journal of Stroke, 1986)
A total of 242 patients with ruptuted intracranial aneurysm was divided into four age groups; (A) 70 and over, (B) 65-69, (C) 60-64, and (D) 59 and less, and studies were made with special reference to aged patients with ruptured intracranial aneurysm of 70 and over of age. In order to ascertain the characteristics of Group A, a comparison was made of clinical grade at time of admission, computed tomography (CT) findings, location of the ruptured aneurusm, complications, timing of aneurysm surgery, reason for conservative treatment, and prognosis among the groups and the following results were obtained. 1) In Group A, the number of cases evaluated to be severe at time of admission was large, 57% belonging to grade IV or V according to the classification of Hunt and Kosnik. The rate of complications was also high. 2) No difference by age could be demonstrated in the grade of subarachnoid hemorrhage on CT. The complication of hydrocephalus was high in Group A, being 26%. 3) Ruptured aneurysm was located in the internal carotid artery in 35% of the cases belonging to Group A. 4) In the early operation group up to day 2, there were many cases of poor prognosis in Group A, but no difference by age could be observed in the operation group after day 3. 5) As for the reasons of conservative treatment, advanced age was given in 19% in Group A and rerupture in 24% in Group D. The foregoing findings suggest that careful evaluation should also be made in considering the indications for surgical treatment of aged patients.